IMPLEMENTATION OF MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) AND MODELING OF QUESTIONNAIRE BASED ON A CASE OF MBKM IN UNIVERSITAS NAHDLATUL ULAMA SURABAYA - Rizqi Putri Nourma Budiarti; Rizki Amalia; Umdatus Soleha; Sri Hartatik; Endang Sulistiyani; Khamida Khamida; Hidayatul Khusnah; Riyan Sisiawan; ary andini (Jurnal Bisnis dan Keuangan, 2022)
Technological developments in the midst of the covid19 pandemic prompted the enactment of a new era in the world of education, namely Merdeka Learn Campus Merdeka (MBKM) where its implementation encourages universities to remain productive in implementing the tridharma, namely teaching, research, community service. The increase in the implementation of MBKM is an effort to improve the competence of students and lecturers at universities in synergizing with the world of work and the industrial world. In addition, there are 8 MBKM schemes designed to facilitate the implementation of a flexible learning curriculum for students. This study aims to describe implementation modeling and provide an overview of the extent of involvement of lecturers, staff and students in the implementation of MBKM at Universitas Nahdlatul Ulama Surabaya (UNUSA). This study uses a qualitative research design in presenting data where the results clearly show that there is a positive increase in the implementation of MBKM education at UNUSA which is described from the major and minor impact models analyzed through the results of the questionnaire from UNUSA community that is relevant to the suitability of MBKM implementation with the direction of the Ministry of Education and Culture. which is stated in the regulation of the Ministry of Education and Culture no. 20 of 2021. The data used in this study is the result of a survey on the implementation of MBKM on lecturers, staff and student respondents with a total sampling of 220 lecturers, 113 students and 3661 students. The percentage of the results achieved included the major influence of the questionnaire, 36.53% of the lecturer respondents who were divided into 5 response groups, 66.67% of students who were divided into 5 respondents and into 5 response groups 75.45groups% of Educators were divided. The percentage of the results achieved included minor influence from the questionnaire, 36.53% of the lecturer respondents who were divided into 7 response groups, 63.03% students were divided into 4 response groups and 63.64% Educators were divided into 7 response groups.